The Effectiveness of Village Consultative Body in Kuningan District in Implementing Legislative Function - Erga Yuhandra; Gios Adhyaksa (UNIFIKASI : Jurnal Ilmu Hukum, 2018)
Village Government has a very significant role in managing social processes in the society. The purpose of this research is to examine the process of village regulations making in Kuningan District and the effectiveness of the Village Consultative Body (BPD) in implementing legislative function. The method used in this research was a juridical-empirical research method. A rational analysis based on juridical references was then conducted through literature and field research. The results showed that the Village Consultative Body as a legislative institution at the lower level has an important role in establishing government legal products to realize checks and balances system and accommodating the society’s aspirations. Normatively, the establishment of village regulations in Sukaharja village is not running properly, and in its implementation, the establishment of village regulation in Sukaharja has not fully contained the principles of good regulations making based on Law Number 12 of 2011 concerning Establishment of Legislation. In its process, there are some stages which are not implemented by both village head and BPD so that the regulation is less effective for the society. The Village Consultative Body has three main functions, namely legislation, supervision, and aspiration. Here, the Village Consultative Body is still less effective in implementing those three functions, especially the legislative function. It can be seen from the period of 2010-2015 in which the legal products produced by the BPD are very low, whereas there are many provisions that should have a legal umbrella in order to create legal certainty for the society. This situation happens because there is a lack of human resources in forming the village regulation draft, and the village government does not understand what the contents of the village regulations that should have a legal umbrella in village regulations making.Pemerintah Desa memiliki peran yang sangat signifikan dalam pengelolaan proses sosial di dalam masyarakat. Tujuan penelitian ini adalah untuk mengetahui dan mengkaji bagaimana proses pembentukan peraturan desa di Kabupaten Kuningan dan evektifitas Badan Permusyawaratan Desa dalam menjalankan fungsi legislasi. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian yuridis-empiris selanjutnya dilakukan analisa rasional berdasarkan acuan yuridis melalui penelitian kepustakaan dan lapangan. Hasil penelitian bahwa Badan Permusyawaratan Desa merupakan lembaga legislatif di tingkat bawah yang mana memiliki peranan penting dalam pembentukan produk hukum pemerintahan desa untuk mewujudkan sistem check and balences dan penyambung lidah masyarakat dalam menyampaikan aspirasi. Secara normatif pembentukan perdes di desa Sukaharja belum sesuai, namun dalam tarap implementasinya dalam pembentukan peraturan desa di desa Sukaharja belum sepenuhnya memuat asas-asas pembentukan peraturan yang baik menurut Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan. Dalam prosesnya masih terdapat tahapan-tahapan yang tidak dijalankan baik oleh kepala desa maupun BPD, sehingga peraturan tersebut kurang berdaya guna bagi masyarakat. Badan Permusyawaratan Desa memiliki tiga fungsi yaitu legislasi, pengawasan, dan menampung aspirasi masyarakat. Dalam menjalankan fungsi legislasi tertutama dalam hal ini masih kurang efektif dilihat dari kurun waktu tahun 2010-2015 produk hukum yang dihasilkan oleh BPD sangat rendah, seyogianya banyak ketentuan yang harus dibuatkan payung hukum agar terciptanya kepastian hukum bagi masyarakat setempat. Hal tersebut terjadi karena masih minimnya sumber daya manusia dalam menyusun draf rancangan perdes, serta pemerintah desa belum memahami apa saja materi muatan dari  peraturan desa yang harus dibuat payung hukum dalam pembuatan perdes.